Selective Translation Complex Profiling Reveals Staged Initiation and Co-translational Assembly of Initiation Factor Complexes - Wagner, Susan (Mol Cell, 2020)
Translational control targeting the initiation phase is central to the regulation of gene expression. Understanding all of its aspects requires substantial technological advancements. Here we modified yeast translation complex profile sequencing (TCP-seq), related to ribosome profiling, and adapted it for mammalian cells. Human TCP-seq, capable of capturing footprints of 40S subunits (40Ss) in addition to 80S ribosomes (80Ss), revealed that mammalian and yeast 40Ss distribute similarly across 5′TRs, indicating considerable evolutionary conservation. We further developed yeast and human selective TCP-seq (Sel-TCP-seq), enabling selection of 40Ss and 80Ss associated with immuno-targeted factors. Sel-TCP-seq demonstrated that eIF2 and eIF3 travel along 5′ UTRs with scanning 40Ss to successively dissociate upon AUG recognition; notably, a proportion of eIF3 lingers on during the initial elongation cycles. Highlighting Sel-TCP-seq versatility, we also identified four initiating 48S conformational intermediates, provided novel insights into ATF4 and GCN4 mRNA translational control, and demonstrated co-translational assembly of initiation factor complexes.